2015
DOI: 10.1021/acs.jpca.5b08011
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Kinetic Model for Description of the Iodate–Arsenous Acid Reaction: Experimental Evidence of the Direct Reaction

Abstract: The autocatalytic iodate-arsenous acid reaction was investigated by a stopped-flow instrument under strongly acidic medium (pH ≤ 1) by monitoring the absorbance-time profiles at 468 nm. The kinetic traces were found to exhibit a perfect sigmoidal shape in stoichiometric excess of iodate with a well-defined and reproducible induction period that depends on the initial concentration of the reactants as well as on the pH. All the experimental curves can be globally fitted by a simple kinetic model involving the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 36 publications
7
13
0
Order By: Relevance
“…Mambo and Simoyi also argued that their iodate solution was contaminated with iodide and the concentration of this species may be as high as 4 μM in their experimental conditions. In contrast to this, our study, however, showed that even if the stock iodate solution contained a trace amount of iodide its concentration could not be higher than approximately 0.005% of the iodate concentration, in agreement with our previous study . It thus corresponds to 5 × 10 –8 M, a value that is significantly smaller than the smallest initial iodide concentration used in our experiments.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Mambo and Simoyi also argued that their iodate solution was contaminated with iodide and the concentration of this species may be as high as 4 μM in their experimental conditions. In contrast to this, our study, however, showed that even if the stock iodate solution contained a trace amount of iodide its concentration could not be higher than approximately 0.005% of the iodate concentration, in agreement with our previous study . It thus corresponds to 5 × 10 –8 M, a value that is significantly smaller than the smallest initial iodide concentration used in our experiments.…”
Section: Resultssupporting
confidence: 87%
“…In contrast to this, our study, however, showed that even if the stock iodate solution contained a trace amount of iodide its concentration could not be higher than approximately 0.005% of the iodate concentration, in agreement with our previous study. 19 It thus corresponds to 5 × 10 −8 M, a value that is significantly smaller than the smallest initial iodide concentration used in our experiments. Consequently, in our case, the inherent iodide contamination of the iodate solution could not play any decisive role in determining the characteristics of the kinetic curves.…”
Section: The Journal Of Physical Chemistry Amentioning
confidence: 73%
See 1 more Smart Citation
“…To unambiguously answer this question, the pH is set to nearly neutral conditions (pH = 6.51) where the arsenous acid-iodate reaction is vanishingly slow. 12 The reactor was a standard quartz cuvette with a 1 cm pathlength. The stirring process was carried out using a 0.9 cm long stirring bar.…”
Section: Resultsmentioning
confidence: 99%
“…10 It is therefore expected that a simpler real chemical system may facilitate the study of the theoretical background of the emergence of stochastic behavior. This expectation, along with the fact that the arsenous acid-iodate reaction exhibits crazy-clock behavior (CCB) as reported recently by our research group, 11 has led us to elucidate the comprehensive kinetic model of the arsenous acid-iodate system, 12,13 including the well-known Dushman 14 and Roebuck 15 reactions. Very recently, Pagnacco et al reported 16 that the state I (low iodide and iodine concentration) to state II (high iodide and iodine concentration) transition of the Briggs-Rauscher reaction 17 after leaving the strongly reproducible oscillatory state was found to be irreproducible as well.…”
Section: Introductionmentioning
confidence: 83%